A review on lipid and polymeric nano-based 17-β-estradiol delivery systems: advances and challenges - Mayara Munhoz de Assis Ramos; Fernanda Yamamoto Ricardo-; Luiza de Oliveira Macedo; Cristiano Jesus Correia; Luiz Felipe Pinho Moreira; Raimar Löbenberg; Ana Cristina Breithaupt-Faloppa; Nadia Bou-Chacra (Frontiers Media S.A., 2024)
17β-estradiol (E2) is an endogenous steroid hormone pivotal for the development of female secondary sexual characteristics and the maintenance of the female reproductive system. Its roles extend beyond these physiological functions, as E2 is employed in hormone replacement therapy to alleviate symptoms associated with menopause. Furthermore, E2 exhibits therapeutic potential in the management of osteoporosis, breast cancer, and various neurological and cardiovascular conditions, partly due to its anti-inflammatory effects via modulation of the MAPK/NFκB signaling pathway. Notwithstanding, the hydrophobic nature of E2 significantly hinders the formulation of efficacious delivery systems for its clinical deployment. Recent advances have highlighted nano-based delivery systems for E2 as a promising solution to this solubility challenge. This review critically examines contemporary nano-delivery strategies for E2, particularly emphasizing lipid and polymeric nanoparticle-based systems. These nanostructures are designed to enhance stability, biocompatibility, controlled release, and targeted delivery of E2, yet the selectivity of E2 delivery for therapeutic purposes remains an ongoing challenge. The novelty of this review lies in its focus on the advances in nano-based E2 delivery systems over the past decade, a topic not extensively covered in prior literature. We present a comprehensive analysis of the encapsulation of E2 within polymeric and lipid nanoparticles, underscoring the untapped potential of these strategies. This review identifies a significant research gap, advocating for intensified experimental investigations that could pave the way for the translation of nano-based E2 therapies from bench to bedside.